SISTEM INFORMASI MANAJEMEN PERTANAHAN NASIONAL PADA KANTOR PERTANAHAN KOTA TERNATE PROVINSI MALUKU UTARA - GALANGBULAENG, VERAWATI OLIVIA; Rumapea, Patar; Rares, joyce Jacinta (Sam Ratulangi University, 2016)
In general, when people talk or hear the term Management Information System (MIS), then reflected in their minds is a system that was created to carry out-processing the data into information to be used by an organization or certain parties who need information about. Based on the identification of the problem, it can be formulated problems in this study, namely: